Improving 1-Year Outcomes of Infrainguinal Limb Revascularization: Population-Based Cohort Study of 104 000 Patients in England. Issue 18 (1st May 2018) - Heikkila, Katriina; Mitchell, David C.; Loftus, Ian M.; Johal, Amundeep S.; Waton, Sam; Cromwell, David A.
Abstract : Background: The availability and diversity of lower limb revascularization procedures have increased in England in the past decade. We investigated whether these developments in care have translated to improvements in patient pathways and outcomes. Methods: Individual-patient records from Hospital Episode Statistics were used to identify 103 934 patients who underwent endovascular (angioplasty) or surgical (endarterectomy, profundaplasty, or bypass) lower limb revascularization for infrainguinal peripheral artery disease in England between January 2006 and December 2015. Major lower limb amputations and deaths within 1 year after revascularization were ascertained from Hospital Episode Statistics and Office for National Statistics mortality records. Competing risks regression was used to estimate the cumulative incidence of major amputation and death, adjusted for patient age, sex, comorbidity score, indication for the intervention (intermittent claudication, severe limb ischemia without record of tissue loss, severe limb ischemia with a record of ulceration, severe limb ischemia with a record of gangrene/osteomyelitis), and comorbid diabetes mellitus. Results: The estimated 1-year risk of major amputation decreased from 5.7% (in 2006–2007) to 3.9% (in 2014–2015) following endovascular revascularization, and from 11.2% (2006–2007) to 6.6% (2014–2015) following surgical procedures. The risk of death after both types of revascularization also decreased. These trends were observed for all indication categories, with the largest reductions found in patients with severe limb ischemia with ulceration or gangrene. Overall, morbidity increased over the study period, and a larger proportion of patients was treated for the severe end of the peripheral artery disease spectrum using less invasive procedures. Conclusions: Our findings show that from 2006 to 2015, the overall survival increased and the risk of major lower limb amputation decreased following revascularization. These observations suggest that patient outcomes after lower limb revascularization have improved during a period of centralization and specialization of vascular services in the United Kingdom. Abstract : Supplemental Digital Content is available in the text.